2007
DOI: 10.1590/s1807-59322007000600012
|View full text |Cite
|
Sign up to set email alerts
|

Elective vs Non-Elective Radial Artery Grafts: Comparing Midterm Results Through 64-Slice Computed Tomography

Abstract: Elective vs non-elective radial artery grafts: comparing midterm results through 64-Slice Computed Tomography. Clinics. 2007; 62(6):725-30.BACKGROUND: Left internal thoracic artery to left anterior descending artery (LITA-LADA) grafting has become a fundamental part of the coronary artery bypass graft procedure (CABG). This grafting in turn has led to an increased use of other arterial conduits, of which the radial artery (RA) is most popular. Whether RA grafting can be used in the emergency patient is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
4
11
0
1
Order By: Relevance
“…There are few reports approaching the use of arterial grafts in emergency surgeries. Our team demonstrated that the CABG, when exclusively performed with LITA and RA, presents good short-and mid-term clinical evolution, as much in elective surgeries as in emergency surgeries, with RA patency of 84% in 4 years [3,4]. Several studies have demonstrated that different RA resection techniques present similar outcomes.…”
Section: Introductionmentioning
confidence: 82%
“…There are few reports approaching the use of arterial grafts in emergency surgeries. Our team demonstrated that the CABG, when exclusively performed with LITA and RA, presents good short-and mid-term clinical evolution, as much in elective surgeries as in emergency surgeries, with RA patency of 84% in 4 years [3,4]. Several studies have demonstrated that different RA resection techniques present similar outcomes.…”
Section: Introductionmentioning
confidence: 82%
“…The rationale for not employing the left thoracic artery in the past in patients with ICM was due to apprehension about complications related to advanced age, urgency of revascularization, and reserved anxiety about long‐term prognosis 16. However, the findings of this study and other recent studies16,17,19-23 suggest that there is little cause for concern. Thus, patients with ICM should be managed with a left internal thoracic artery graft when revascularization is selected therapy 15.…”
Section: Discussionmentioning
confidence: 72%
“…Failure to previously demonstrate an association on ICM between the sort of graft for bypass and long‐term coronary events by other investigators may be related to the decreased application of the left internal thoracic artery (i.e., between 20% and 35% when informed) 7. The rationale for not employing the left thoracic artery in the past in patients with ICM was due to apprehension about complications related to advanced age, urgency of revascularization, and reserved anxiety about long‐term prognosis 16. However, the findings of this study and other recent studies16,17,19-23 suggest that there is little cause for concern.…”
Section: Discussionmentioning
confidence: 99%
“…First reports about using the LITA routinely for sequential grafting of a diagonal branch and the LAD were published in the mid 1990s [7]. At 52 months after surgery, patency of sequential LITA grafts to a diagonal branch and the LAD was found to be 79% in a relatively small number of 14 patients [8].…”
Section: Discussionmentioning
confidence: 99%